A Model for a Structured Clinical Development Program for First-Year Residents: Utilizing the Entrance OSCE, Individualized Learning Plans (ILPs), and Peer Clinical Coaching - Jill Krapf; Sameer Aggarwal; Benjamin Blatt; Larrie Greenberg (Association of American Medical Colleges, 2015)
Abstract Introduction Identification of incoming residents' unique strengths and weaknesses in a clinical setting is important for developing an individualized educational curriculum and addressing specific needs. This resource presents and describes materials for a clinical development program for first-year residents. Methods The program is structured around three educational elements: an entrance objective structured clinical examination (OSCE), an individualized learning plan (ILP), and peer clinical coaching. The included files that describe these three elements serve as a resource for residency directors and/or graduate medical education faculty interested in constructing a similar program. In the program, first-year OB-GYN residents participated in an entrance OSCE as a component of their orientation to residency. Their performance was evaluated through faculty and self-assessment tools and scored on a 9-point scale in accordance with the Accreditation Council for Graduate Medical Education's core competency scoring evaluation system. These evaluations were utilized in the creation of ILPs. Stated goals were translated into discrete learning objectives and then developed further through a learning strategy and time line using the SMART model. As a component of a research study, first-year residents were randomized into one of two groups: clinical coaching group or individual implementation group. Senior resident volunteers served as peer clinical coaches after participating in a 2-hour interactive workshop. The peer clinical coaches met with first-year residents on a monthly basis for 4 months to develop the resident's ILP. Exit questionnaires were completed at the conclusion of the yearlong program. Results Residents in both groups felt very positive about developing their ILPs, emphasizing that the program helped to map out their goals in preparation for midyear reviews. First-year residents in the clinical coaching group reported that the intervention improved their clinical experience. First-year residents who implemented the ILP alone indicated that their clinical experience was somewhat worse. Discussion The OSCE is a well-utilized tool for ensuring direct observation, evaluating clinical performance in a simulated environment, and providing timely feedback. Another potential application of the OSCE is to provide a baseline evaluation of clinical performance that may be used in determining a starting point for clinical competencies. Utilizing the feedback from the OSCE to create an ILP can translate valuable feedback into measurable objectives and competencies, while also providing a model for reassessment and follow-up.